2001
DOI: 10.1097/00000658-200104000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Denervated Stomach as an Esophageal Substitute Recovers Intraluminal Acidity With Time

Abstract: ObjectiveTo determine whether the denervated stomach as an esophageal substitute recovers normal intraluminal acidity with time. Summary Background DataBilateral truncal vagotomy to the stomach as an esophageal substitute reduces both gastric acid production and antral motility, but a spontaneous motor recovery process takes place over years. MethodsIntraluminal gastric pH and bile were monitored during a 24-hour period 1 to 195 months after transthoracic elevation of the stomach as esophageal replacement in 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 27 publications
3
91
1
6
Order By: Relevance
“…The first evidence of normal morphological structural restoration and independence from external inputs is electronomicroscopically identified and confirmed by pH-metric evaluation/ 24h (16,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 84%
“…The first evidence of normal morphological structural restoration and independence from external inputs is electronomicroscopically identified and confirmed by pH-metric evaluation/ 24h (16,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 84%
“…Gutshow et al [11] noted that early after vagotomy intralu minal acidity decreased in two -thirds of the patients, but the stomach recovered its normal pH profile with time. They show that the denervated stomach as an esophageal substitute recovers a normal intralu minal acid ity with time, so that more than 3 years after surgery.…”
Section: Esophageal Exposure To Acid and Duodenal Juicementioning
confidence: 99%
“…The same procedure in relat ion to subtotal esophagectomy may dramatically impair acid s ecretion by the gastric transplant as an esophageal substitute at early follow-up as attested to by the reduction in both basal and peak acid outputs by 83% and 30%, respectively [11]. Theoretically, gastric tubulization should reduce the parietal cell mass , further reducing the acid secretion capacity.…”
Section: Esophageal Exposure To Acid and Duodenal Juicementioning
confidence: 99%
See 1 more Smart Citation
“…5 Patients who have had an oesophagectomy with gastric pull-up frequently suffer from severe reflux due to the acid secretion in the gastric conduit. 6 Previous studies have shown that up to 35% of patients (at three years) will have oesophagitis, with some developing columnar metaplasia. 7 This therefore has a huge impact when considering the long-term implications of oesophagectomy for those with benign conditions.…”
mentioning
confidence: 99%